Norms detection and assimilation in multi-agent systems: a conceptual approach - Ahmed Mahmoud, Moamin; Ahmad, Mohd Sharifuddin; Ahmad, Azhana; Mohd Yusoff, Mohd Zaliman; Mustapha, Aida (Springer, 2012)
In this paper, we propose a technique for a software agent to detect the norms of a community of agents and assimilate its behaviour to comply with the local normative protocol, failing which, the agent is refused services and resources. In this technique, the software agent is equipped with an algorithm, which detects and analyzes the normative interactions between local agents. When the detection is successful, it launches another algorithm to request for its assimilation to the local normative protocol, indicating its acceptance by the group of local agents.